Hospital Financial Strategy in Response to COVID-19: A Systematic Review - Yulius, Suci Kirana; Soewondo, Prastuti; Carolinsia, Brenda (Journal of Health Policy and Management, 2022)
Background: The COVID-19 pandemic had resulted in an unprecedented strain on healthcare systems. Hospitals are faced with the unexpected influx of patients, increasing need for protection equipment and infection control procedures, increased workload and operational hours, and the depleting revenues due to closure of elective services. This study aims to further analyze the financial strategies used by hospitals to ensure its operations and to overcome financial challenges presented by the COVID-19 pandemic.Subjects and Method: A systematic review has been identified using four databases: MEDLINE (PubMed), Google Scholar, SCOPUS, and MedSci. This search in literature was published articles from January 2020 to June 2021 using PRISMA guidelines. The keywords used “COVID-19” OR “SARS-CoV-2” AND (ii) "hospital" OR "hospital cost" OR "cost" AND (iii) "strategy" OR "financial strategy" OR "economic" OR "economic analysis".Results: 6 studies were included in our final analysis. We found that effective financial strategies to cover for reduced revenues and increasing cost of care include: (1) Ensuring incentives from external agencies, including the government; (2) Creating new budgets or modifying existing budgets to cover for COVID-19-related cost of care; and (3) Use of contactless health system such as telehealth. Specifically for modifying existing budgets, studies have found that implementing proper health protocol and infection control measures is the most effective, as it has been reported to yield a return of investments.Conclusion: Government funds and relief aids remain the most important source of financial support for hospitals in caring for COVID-19 patients. Without sufficient financial support, hospitals have to get creative in adding additional service fees or finding innovative solutions such as telehealth to cover the dwindling revenues from their closed service units.Keywords: COVID-19, hospital cost, financial strategiesCorrespondence: Suci Kirana Yulius. Hospital Administration Studies Program, Faculty of Public Health, Universitas Indonesia. Universitas Indonesia Pondok Cina, Beji, Depok City, West Java. Mobile: 081273874947. Email: suci.kirana@ui.ac.id.Journal of Health Policy and Management (2002), 07(01): 81-93https://doi.org/10.26911/thejhpm.2022.07.01.08